A study on the competencies and personal traits of students to become knowledge workers: among final year bachelor information studies of UiTM Kedah / Norbaiti Aling - Aling, Norbaiti (Faculty of Information Management, 2011)
Knowledge workers in today's workforce are individuals who are valued for their ability to interpret information within a specific subject area. Knowledge work is that it is an activity that either requires specialized knowledge ex skills, or creates new knowledge. In contrast to physical labour, knowledge work focuses primarily on creating or applying information or knowledge to create value. Knowledge workers may be found across a variety of information technology roles, but also among professionals like teachers, lawyers, architects, physicians, nurses, engineers and scientists. This study is tending to determine the competencies and personal traits of students to become knowledge worker among Final Year Degree Students of Bachelor in Information Studies. BIS students are chosen as a sample because they have been equipped with element of knowledge workers in certain subject. It will cover the competencies includes skills and knowledge of students needed to become knowledge workers. Besides that, it also used to examine whether the students have a good personal traits pertaining innovative, leadership and openness of experience to become a knowledge worker.